Upaya Pencegahan Anemia pada Balita melalui Pemberian Makanan Bergizi Seimbang - Suci Rahmanda; Hani Ramadani; Muhammad Landung Mukti Ritonga (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Anemia in toddlers is a serious nutritional problem that impacts physical growth, cognitive development, and the child's immune system. This study aims to provide an overview of the level of knowledge, attitudes, and practices of parents in preventing anemia in toddlers. This quantitative study involved 50 respondents using a structured questionnaire instrument covering the domains of knowledge, attitudes, practices, and sources of health information. The results showed that respondents' knowledge was in the adequate category; although all respondents (100%) understood the negative impact of anemia on growth and intelligence, only 80% understood the technical definition and clinical symptoms accurately. In the attitude domain, respondents showed a very positive response (100%) to the importance of balanced nutrition and early prevention. Regarding the practical aspect, although regular visits to integrated health posts (Posyandu) reached 100%, the consistency of daily animal side dish intake remained at 80%. An interesting finding showed a shift in information sources, with social media (80%) dominating over direct exposure to information from health workers (40%). This study concluded that there is a gap between positive attitudes and consistent daily practices, and the need to optimize health education through digital media by medical personnel to reduce the incidence of anemia in toddlers.